Framing the wall: The Palestinian resistance against the occupation in Five Broken Cameras (2011) - Amaral, Diego Granja do (Logos, 2020)
This paper looks at the documentary Five Broken Cameras (Palestine, Israel, France, Netherlands, 2011) to discuss the temporal implications of a quotidian under occupation. More specifically, the investigation casts light over the peaceful resistance against the Israeli wall in the Palestinian village of Bil’in portrayed by the lenses of Emad Burnat, a Palestinian villager who becomes the village´s filmmaker after the acquisition of his first camera. Upon the analysis, I claim that in the context of the Palestinian struggle, cinema is both an integral part of the resistance and an instrument to structure the experience of time in an area fragmented by the occupation.